Replacement of bar-clip retention system by Equator in overdenture on implant (Research, Society and Development, 2021)
The oral rehabilitation of a total edentulous patient requires attention for its correct evaluation, careful planning and adequate planning. The present work reports a case of replacement of the bar-clip retention system by the Equator system of a lower overdenture. A 70-year-old female patient attended the extension project “Overdenture for total toothless in geriatrics”, complaining about a large lingual volume of her lower prosthesis, making it difficult to eat and phonetics and successive fractures of that prosthesis. The intraoral clinical examination revealed the presence of an upper total prosthesis and a lower overdenture with the bar-clip retention system, in which the spatial position of the bar was inadequate and invaded the tongue space. It was planned to manufacture new prostheses and to replace the bar-clip retention system with independent systems. When taking the lower plaster model in the eyeliner, it was possible to verify that there was a discrepancy in the inclination of the implants greater than 14º, thus selecting the Equator system, which allows the capture of implants with up to 30º of discrepancy. This case highlights the need for reverse planning for the performance of implant surgery, so that a correct retention system is chosen during planning and the surgical stage is performed in order to meet this planning. After the placement of new prostheses and the new retention system, the patient reported a significant improvement in diet and phonetics, as well as in the aesthetics of the prostheses, generating physical, psychological and social well-being.